Illocutionary Speech Acts in the Language Used by Sales Promotion Girls at Unilever Company - RAMADHANI, IMA (LANTERN (Journal on English Language, Culture and Literature), 2013)
Every human being has different communication goal as the others. Language is a combination of words which is used as a medium of communication. Pragmatics studies the particular meaning of language in use. This study takes the conversation of sales promotion girls at the Unilever Company. The writer chose the Unilever Company because the company is a benchmark in the communication service. The purpose of this study is to determine the kinds of illocutionary acts in the utterances spoken by sales promotion girls. The writer analyzed the data by applying Searle’s (1979:23) theory for speech acts and andYule’s(1996:19) for illocutionary speech acts theory. The result of this study showsthat there are five kinds of illocutionary acts which are directive, expressive, declarative, commisive and representative. Among these illocutionary acts, directive is the most dominant kind.Directivespeech acts are aimed to persuade the listener to do something. Key Words: Pragmatics, Illocutionary speech acts and sales promotion girls.